Prognostic significance of expression of cyclooxygenase‐2, vascular endothelial growth factor, and epidermal growth factor receptor in nasopharyngeal carcinoma. Issue 9 (13th September 2012) - Pan, Jianji; Tang, Tianlan; Xu, Luying; Lu, Jiade J.; Lin, Senan; Qiu, Sufang; Chen, Gang; K. Tham, Ivan W.
Abstract Background The association between expression of cyclooxygenase‐2 (COX‐2), vascular endothelial growth factor (VEGF), epidermal growth factor receptor (EGFR), and the long‐term outcomes in treated nasopharyngeal carcinoma (NPC) was studied. Methods Expression of COX‐2, VEGF, and EGFR by immunohistochemical (IHC) staining was assessed in 128 patients with NPC. Overall survival (OS), disease‐free survival (DFS), locoregional control, and distant metastasis‐free survival rates were compared for different expression levels of each marker. Multivariate analysis was by the Cox regression model. Results Median follow‐up after radiation therapy ± chemotherapy was 116 months. Univariate and multivariate analyses demonstrated that COX‐2, VEGF, EGFR, and clinical stage were all independent predictors for OS, DFS, locoregional control, and distant metastasis–free survival rates. Conclusions High expression of COX‐2, VEGF, and EGFR were independent adverse prognostic factors for long‐term outcomes in nonmetastatic NPC independent of clinical stage. © 2012 Wiley Periodicals, Inc. Head Neck, 2013